(untitled) (Phenomenology, Humanities and Sciences, 2023)
Let’s make a list of the ten philosophers that we like the most. Let’s do the same with sociologists, anthropologists or whatever discipline we want. The result of that list, I bet, will be the remarkable evidence of colonialism sedimented in our culture. None of those names will be, With few exceptions, a name proper to Our America. All, if not the vast majority, They will be European characters who populate school and university programs and who, although valuable, they have managed to stifle interest and fuel contempt for Latin American intellectual production. Turning our gaze towards our own sources was the task that, with militant, defined the intellectual career of Enrique Dussel.